Advances in Understanding Intrusive, Explosive and Effusive Processes as Revealed by the Borehole Dilatometer Network on Mt. Etna Volcano - Bonaccorso, Alessandro; Currenti, Gilda; Linde, Alan; Sacks, Selwyn; Sicali, Antonino (Frontiers in Earth Science, 2020)
We present the updated main results obtained from the high precision strain recorded by the borehole dilatometer network on Mt. Etna volcano. The instruments, installed from the end of 2011, detected significant changes during different types of eruptive activity: several lava fountains during 2011-2014; two explosive sequences in 2015 and 2016; moderate effusive activity in 2017 and a dike intrusion in 2018. The strain changes provided powerful diagnostic information on the different ongoing processes, and allowed us to add key information on the different eruptive styles and sources. We also highlight how the recorded signals, with the associated modeling and interpretation, provide a powerful contribution to surveillance requirements on an active volcano. This report demonstrates that the borehole dilatometer network represents a useful tool both for the understanding of the volcano processes and for surveillance needs.